DU ROMAN AU THÉÂTRE : RÉFLEXIONS PRATIQUES ET THÉORIQUES SUR L’ADAPTATION - Pavis, Patrice (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
To deal with the question of adaptation, I use my own adaptation of the first chapter of my novel, Poème toi-même (2021) explaining in footnotes the main choices I had to make and why. I then describe my ideas on adaptation for the theatre (text and performance), and finally attempt to sketch a general theory of adaptation for the stage.